SANTRI BERIJTIHAD: MUNGKINKAH? - Muhammad Adib (JURNAL PUSAKA, 2015)
Ijtihad is mandatory in Islam, but it became an impossible dream since the fatwa of closing of the doors of ijtihad and the enactment of various hard and complex terms for mujtahid qualification. However,scholars have sought to soften the terms of ijtihad by offering the concept of tajazzuâ€™ al-ijtihÄd, ijtihÄd jamÄâ€˜Ä« up to critical muqallid. What about the so called santris? Could the students perform ijtihad? Ijtihad is not impossible, indeed, for santris, especially at the level three (critical muqallid). Such taqlid can be categorized as taqlid manhajÄ«. Moreover, those santris had been doing this latest version of ijtihad, including through bahtsul masail forum. However, this forum still must be addressed on several aspects, such as expanding the studies discipline (interdisciplinary), analyzing the impact of decisions on social transformation, as well as maximizing of publication and collection of feedback.Keywords: ijtihad, santri, taqlid.